PENINGKATAN KUALITAS DISKUSI MELALUI RUBRIK (IMPROVING DISCUSSING QUALITY BY RUBRIC) - Samadhy, Umar (Universitas Negeri Semarang, 2011)
Discussing was a popular method in PGSD departement because this method wais cheap and easy. It was always used in Bahasa Indonesia lecturing. The quality of discussing was low because less participans. The quality of discussing was improved by classroom action research. The result of the research was the quality could be improved by using the opened rubric. According to the research, was suggested to use the open rubric. Key Words: discussing, rubric